Japanese Response to Indonesian Law Banning the Export of Raw Minerals - Tai Fang Yi (Universitas Pelita Harapan, 2017)
The government of Indonesia enacted a policy banning the export of raw minerals in 2009, materialized in Law No. 04 of 2009 on Mineral and Coal Mining. The law mandated the raw minerals processing inside the country before they can be exported to other countries by the year 2014. This policy has drawn response from the government of Japan as one of the importing countries. Japan had threatened to report to the World Trade Organization regarding the issue because they complained that the policy violates the General Agreement on Tariffs and Trade. This study discusses how the policy is in the effort of Indonesia to develop its nation without any intention to harm any other countries. The justification of the enactment of the policy is mandated under the 1945 Constitution and the policy in essence does not deny the General Agreement on Tariffs and Trade. The enactment of the policy has affected the raw minerals export activity in Indonesia when export activity reached its peak in 2013 and also the last year raw material export was allowed. The policy might also have impacts on Japanese mining industries which relies on the import of raw minerals from Indonesia and those having investments in Indonesian mining industries. Japan at the end cancelled its intention to report Indonesia to the World Trade Organization and agreed to solve the dispute through bilateral solutions.BAHASA INDONESIA ABSTRAK: Pemerintah Indonesia memberlakukan kebijakan yang melarang ekspor mineral mentah pada tahun 2009 yang terwujud dalam Undang-Undang No. 04 Tahun 2009 tentang Pertambangan Mineral dan Batubara. Undang-Undang tersebut mengamanatkan pemrosesan mineral mentah di dalam negeri sebelum dapat diekspor ke negara lain mulai dari tahun 2014. Kebijakan ini telah menarik tanggapan dari pemerintah Jepang sebagai salah satu negara pengimpor. Jepang telah mengancam untuk melapor kepada Organisasi Perdagangan Dunia mengenai masalah ini karena mereka mengeluhkan bahwa kebijakan tersebut melanggar Persetujuan Umum tentang Tarif dan Perdagangan. Studi ini membahas bagaimana kebijakan tersebut adalah upaya Indonesia untuk mengembangkan negaranya tanpa ada niat untuk menyakiti negara lain. Pembenaran atas berlakunya kebijakan tersebut diamanatkan di bawah UUD 1945 dan pada intinya, kebijakan tersebut tidak menyalahi Persetujuan Umum tentang Tarif dan Pertambangan. Pemberlakuan kebijakan tersebut telah mempengaruhi aktivitas ekspor mineral mentah di Indonesia di mana kegiatan ekspor mineral mentah paling tinggi pada tahun 2013 yang merupakan tahun terakhir di mana mineral mentah diizinkan untuk diekspor. Kebijakan tersebut memiliki dampak yang mungkin terjadi bagi industri pertambangan Jepang yang mengandalkan impor mineral mentah dari Indonesia dan yang memiliki investasi di industri pertambangan Indonesia. Jepang pada akhirnya membatalkan niatnya untuk melaporkan Indonesia ke Organisasi Perdagangan Dunia dan sepakat untuk menyelesaikan perselisihan tersebut melalui solusi bilateral.